RNA-Sequencing Analysis of Messenger RNA/MicroRNA in a Rabbit Aneurysm Model Identifies Pathways and Genes of Interest - Holcomb, M.; Ding, Y.-H.; Dai, D.; McDonald, R.J.; McDonald, J.S.; Kallmes, D.F.; Kadirvel, R. (American Journal of Neuroradiology, 2015)
BACKGROUND AND PURPOSE: Rabbit aneurysm models are used for the testing of embolization devices and elucidating the mechanisms of human intracranial aneurysm growth and healing. We used RNA-sequencing technology to identify genes relevant to induced rabbit aneurysm biology and to identify genes and pathways of potential clinical interest. This process included sequencing microRNAs, which are important regulatory noncoding RNAs.MATERIALS AND METHODS: Elastase-induced saccular aneurysms were created at the origin of the right common carotid artery in 6 rabbits. Messenger RNA and microRNA were isolated from the aneurysm and from the control left common carotid artery at 12 weeks and processed by using RNA-sequencing technology. The results from RNA sequencing were analyzed by using the Ingenuity Pathway Analysis tool.RESULTS: A total of 9396 genes were analyzed by using RNA sequencing, 648 (6.9%) of which were found to be significantly differentially expressed between the aneurysms and control tissues (P < .05; false-discovery rate, <0.01; fold change, >2 or <.5). Of these genes, 614 were mapped successfully, 143 were down-regulated, and 471 were up-regulated in the aneurysms as compared with controls. Using the same criteria for significance, 3 microRNAs were identified as down-regulated and 5 were identified as up-regulated. Pathway analysis associated these genes with inflammatory response, cellular migration, and coagulation, among other functions and pathologies.CONCLUSIONS: RNA-sequencing analysis of rabbit aneurysms revealed differential regulation of some key pathways, including inflammation and antigen presentation. ANKRD1 and TACR1 were identified as genes of interest in the regulation of matrix metalloproteinases.IPAIngenuity Pathway AnalysismiRNAmicroRNA